2008
DOI: 10.1093/ndt/gfn720
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors in typical haemolytic uraemic syndrome

Abstract: These results highlight the role of glycoprotein 1balpha in the physiopathology of typical forms of HUS and show that the genetic background plays a role in the susceptibility and severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…However, linkage analysis has indicated that the risk of developing D ϩ HUS is associated with the 145M allele of platelet glycoprotein Ib␣ with an odds ratio of 3.08 (P Ͻ .001). 26 This variant of glycoprotein Ib␣ binds VWF with higher affinity than the more common 145T allele, which suggests that increased VWF-dependent platelet adhesion promotes tissue injury in children infected with Stx-producing E coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, linkage analysis has indicated that the risk of developing D ϩ HUS is associated with the 145M allele of platelet glycoprotein Ib␣ with an odds ratio of 3.08 (P Ͻ .001). 26 This variant of glycoprotein Ib␣ binds VWF with higher affinity than the more common 145T allele, which suggests that increased VWF-dependent platelet adhesion promotes tissue injury in children infected with Stx-producing E coli.…”
Section: Discussionmentioning
confidence: 99%
“…However, linkage analysis has indicated that the risk of developing D ϩ HUS is associated with the 145M allele of platelet glycoprotein Ib␣ with an odds ratio of 3.08 (P Ͻ .001). 26 This variant of glycoprotein Ib␣ binds VWF with higher affinity than the more common 145T allele, which suggests that increased VWF-dependent platelet adhesion promotes tissue injury in children infected with Stx-producing E coli.Stx B subunits induce the secretion of VWF by activating signaling pathways that require binding to cell surface Gb3, 8 but these pathways diverge initially for Stx1B and Stx2B. Stx1B-induced VWF secretion depends on a transient rise in intracellular Ca 2ϩ and activation of PKC␣ (Figures 4 and 5); in contrast, Stx2B-induced VWF secretion is independent of intracellular Ca 2ϩ and PKC␣ but depends on protein kinase A.…”
mentioning
confidence: 99%
“…6,8 Whether Stxinduced VWF secretion contributes to the pathogenesis of D ϩ HUS in humans is unknown, but such a role would be consistent with a recent linkage analysis. The risk of developing D ϩ HUS was associated (odds ratio, 3.08; P Ͻ .001) with the expression of a platelet GPIb␣ 145M variant that binds VWF with higher affinity than the more common GPIb␣ 145T variant, 22 suggesting that increased Stx-induced interactions between VWF and platelets may promote renal injury in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent linkage analysis are consistent with this hypothesis: the risk of developing D ϩ HUS was associated (odds ratio 3.08, P Ͻ .001) with expression of the platelet GPIb␣ 145M polymorphic variant, which has greater affinity for VWF than the more common GPIb␣ 145T variant. 22 Stx1 and Stx2 both bind Gb3 and use the same mechanism to inactivate ribosomes. However, Stx2 causes D ϩ HUS more often than does Stx1, and this difference has not been explained.…”
Section: Discussionmentioning
confidence: 99%